An Investigation Into Factors Affecting Access to Financial Services in Farmers' Suicide Prone Bundelkhand Region of India - Yadav, Priyanka; Sharma, Anil K. (Indian Journal of Finance, 2018)
Finance is the basis of all economic activities. The importance of access to finance by one and all on an equitable basis for sustainable development of a nation has been well documented in the literature. However, mere opening of a savings account cannot serve the purpose of complete financial inclusion unless the financial services are used on a regular basis by the people. In this context, this paper made an attempt to study factors which are associated with financial inclusion by way of two parameters - using a bank account for deposit/withdrawal and using credit from institutional sources in rural India. For this purpose, data were collected from Bundelkhand region of India where farmer suicides is one of the most burning issues. The results showed that gender, age, and size of landholding were statistically significant in predicting the probability of an individual being financially included or not.